'If I tried this idea again: developing faculty professional growth through reflective practice. Issue 6 (2nd November 2018) - Burgoyne, Mary Beth; Chuppa-Cornell, Kim
ABSTRACT: This article discusses the results of a 2-year faculty professional growth project in which a library faculty employed reflective and deliberate practice techniques regarding their instruction of information literacy outcomes. The faculty submitted reflections through a Google-forms tool, which was used to identify and assess essential elements of effective teaching and learning. The project's longitudinal data was analyzed each semester and academic year, and evidence was found of faculty growth in their application of active learning techniques as well as growth in their reflective writing.